CFD model as a digital twin of the radiation state of the new safe confinement of the chernobyl NPP - Krukovskyi, P.G.; Diadiushko, Ye.V.; Garin, V.O.; Tryfonov, O.V.; Kabanov, Yu.Yu. (Вопросы атомной науки и техники, 2020)
The necessity of a detailed analysis and prediction of the operating parameters and distribution of radioactive aerosols (RA) in the Shelter Object (SO), the New Safe Confinement (NSC) and the environment of the Chernobyl NPP over the 100–year life of the NSC during the extraction of radioactive waste (RW) from the SO is being justified. For this, a computer CFD (Computational Fluid Dynamic) model has been developed that allows the analysis, prediction and control of the thermogasdynamic, humidity and radiation states of the NSC. The issues of ensuring the adequacy of the model to the various NSC states during long–term operation on the basis of modern technologies of the so–called selflearning “Digital Twin” (Digital Twin) and CFD monitoring of especially important and dangerous objects, especially nuclear, are being considered.